Islamic Values Dalam Pembentukan Karakter di Era Millennial - Kurjum, H. Mohammad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
Nowadays has been known as millennial epoch. The great era has been going on influencing the human character. This is because of the opened acces from foreign culture toward Indonesian ones by technological view. Therefore, we must be well informed as the millennial generation partner. We must change the bad culture to be a good one. Millenial era has been noted as a globalization era dealing with the Information developed. The character of someones was influenced by the environment as well. Islam, however, gives the solution in developing character of human being, even deep values which is implemented to daily lives. Islamic Valuses taught ; Akhlaq Al-kariimah, Ibadah amaliyah, Tauhiid, Tolerance, Dedication and loyalty, Amanah dan responsibility,and many others. These values aim at implementing the characters to be Islamic oriented, specially focusing on social, economy, politics and culture. Those are to be oriented as Islamic Values in order to be better in the millennial life